JUSTICE-BASED HEALTH LAW: STUDY OF PROFESSION EQUALITY-BASED JUSTICE ON SOCIAL JUSTICE - Muhammad Taadi Samsuri; Khudzaifah Dimyati; A Absori (Jurnal Dinamika Hukum, 2018)
The realization of the right to health can be achieved through several different approaches, for example; the establishment of health policies or the implementation of programs established by World Health Organization (WHO), or the adoption of legal instruments. This research is a doctrinal normative law research, that is by reviewing and analyzing library materials or secondary data that examines the values of justice through statutory approach. As a complement, this research also uses case approach, through field study. The discussion uses John Rawls's justice concept with fairness justice to analyze the findings of both research related to the findings of legislation and field findings, with the conclusion that justice based health law based on profession equality based on social justice is realized with health law that reflects the values of justice, the right of professional equality as well as the value of social justice with the concept of justice as a fairness as a capable concept to adapt, so it needs an adaptive health law approach.Keywords: Health Law, Profession Equality, Social Justice